Angle resolved photoelectron spectroscopy of two-color XUV–NIR ionization with polarization control. (4th August 2016) - Düsterer, S; Hartmann, G; Babies, F; Beckmann, A; Brenner, G; Buck, J; Costello, J; Dammann, L; Fanis, A De; Geßler, P; Glaser, L; Ilchen, M; et al.
Abstract: Electron emission caused by extreme ultraviolet (XUV) radiation in the presence of a strong near infrared (NIR) field leads to multiphoton interactions that depend on several parameters. Here, a comprehensive study of the influence of the angle between the polarization directions of the NIR and XUV fields on the two-color angle-resolved photoelectron spectra of He and Ne is presented. The resulting photoelectron angular distribution strongly depends on the orientation of the NIR polarization plane with respect to that of the XUV field. The prevailing influence of the intense NIR field over the angular emission characteristics for He(1s) and Ne(2p) ionization lines is shown. The underlying processes are modeled in the frame of the strong field approximation (SFA) which shows very consistent agreement with the experiment reaffirming the power of the SFA for multicolor-multiphoton ionization in this regime.